SUSTAINABILITY OF ENDOWMENT FUND IN THE SULTANATE OF OMAN: A CONCEPTUAL STUDY - Haza Juma Khamis Al Bekari; Kamisah Supian (Journal of Islamic, Social, Economics and Development, 2019)
Endowment properties, all over the world, seem to be in a state of disarray, dilapidated, mismanaged, unaccounted for or underutilized, wasting the valuable resource created by successive generation of Muslims for the benefit of the ummah. However, any initiative aimed at regenerating the endowment worldwide faces obstacles due to the lack of relevant research, feasible strategies, knowledge and coordination among the various stakeholders involved. Oman is a country which has huge assets of endowment fund, however, vast endowment leads to mismanagement, corruption, abuse and poor structure as well as less transparency. Thus, this paper is aiming to investigate the connection between endowment fund in Oman and the ability to sustain for coming years. The study contributes to create innovations methods to sustain Omani assets of endowment to use it in developing Omani Societies. This study focuses on sustaining Omani societies economically and socially using the assets of Omani endowment, however, the methods which has been suggested might has some limitation, but still some methods can be implemented in Oman.